Effect of Different EndoAnchor Configurations on Aortic Endograft Displacement Resistance: An Experimental Study. (October 2019) - Goudeketting, Seline R.; Vermeulen, Jenske J. M.; van Noort, Kim; te Riet o. g. Scholten, Gerben; Kuipers, Henny; Slump, Cornelis H.; de Vries, Jean-Paul P. M.
Purpose: This study investigated the effect of different EndoAnchor configurations on aortic endograft displacement resistance in an in vitro model.Materials and Methods: An in vitro model was developed and validated to perform displacement force measurements on different EndoAnchor configurations within an endograft and silicone tube. Five EndoAnchor configurations were created: (1) 6 circumferentially deployed EndoAnchors, (2) 5 EndoAnchors within 120° of the circumference and 1 additional, contralateral EndoAnchor, (3) 4 circumferentially deployed EndoAnchors, (4) 2 rows of 4 circumferentially deployed EndoAnchors, and (5) a configuration of 2 columns of 3 EndoAnchors. An experienced vascular surgeon deployed EndoAnchors under C-arm guidance at the proximal sealing zone of the endograft. A constant force with increments of 1 newton (N) was applied to the distal end of the endograft. The force necessary to displace a part of the endograft by 3 mm was defined as the endograft displacement force (EDF). Two video cameras recorded the measurements. Videos were examined to determine the exact moment 3-mm migration had occurred at part of the endograft. Five measurements were performed after each deployed EndoAnchor for each configuration. Measurements are given as the median and interquartile range (IQR) Q1, Q3.Results: Baseline displacement force measurement of the endograft without EndoAnchors resulted in a median EDF of 5.1 N (IQR 4.8, 5.2). The circumferential distribution of 6 EndoAnchors resulted in a median EDF of 53.7 N (IQR 49.0, 59.0), whereas configurations 2 through 5 demonstrated substantially lower EDFs of 29.0 N (IQR 28.5, 30.1), 24.6 N (IQR 21.9, 27.2), 36.7 N, and 9.6 N (IQR 9.4, 10.0), respectively. Decreasing the distance between the EndoAnchors over the circumference of the endograft increased the displacement resistance.Conclusion: This in vitro study demonstrates the influence EndoAnchor configurations have on the displacement resistance of an aortic endograft. Parts of the endograft where no EndoAnchor has been deployed remain sensitive to migration. In the current model, the only configuration that rivaled a hand-sewn anastomosis was the one with 6 EndoAnchors. A circumferential distribution of EndoAnchors with small distances between EndoAnchors should be pursued, if possible. This study provides a quantification of different EndoAnchor configurations that clinicians may have to adopt in clinical practice, which can help them make a measured decision on where to deploy EndoAnchors to ensure good endograft fixation.